Evaluating Soil Particle Analysis Methods for Tropical Andosols in Indonesia - Anindita, Sastrika; Sandrawati, Apong; Arifin, Mahfud; Devnita, Rina (Soilrens, 2024)
Choosing the right method to quantify soil particles (sand, silt, clay) is essential to predict and managesoil characteristics in relation to e.g. nutrient or water retention. However, separating silt and clayparticles for volcanic soils is difficult. In this study, we investigated the effect of three different soilparticle analysis methods, namely the regular pipette method, Na-resin dispersion, andultrasonication with high energy level (1500 J ml-1) on the distribution of soil particle size in tropical volcanic soils. Ultrasonication with high energy level was founded to be the best method to fullyseparate silt and clay fraction compared to Na-resin and regular pipette method. In conversion, thedispersion of soil particles using regular pipette method was suboptimal. In the ultrasonicationmethod, a step that is important to achieve full dispersion is pH buffer > 8 in soil suspension. Thisultrasonication method was founded to have good correlation with Na-resin dispersion method (R =0.88). This study suggested that conventional particle size analysis may not fully separate sand, silt,and clay particles correctly in soils rich in amorphous materials and oxides, and we proposedultrasonication high energy level with pH buffer > 8 method as an alternative method.